Analysis of Fiqh Muamalah in Sharing Economy Practices: Case Study of Grab, Gojek, and AirBnB - Ar'rum Adrianti (ekonomi syariah, 2025)
This study aims to analyze the sharing economy from the perspective of fiqh muamalah, focusing on digital economic practices such as ride-sharing services (Grab, Gojek) and application-based accommodations (Airbnb). The sharing economy phenomenon has shifted ownership patterns to access-based usage of assets, which presents various legal implications in transactions. This research employs a descriptive qualitative approach through literature review and analysis of relevant fatwas issued by the Indonesian National Sharia Council (DSN-MUI). The findings reveal that most sharing economy practices are acceptable within the muamalah framework, as long as they adhere to the principles of justice, transparency, and are free from elements of gharar (uncertainty) and riba (usury). However, there remain ambiguities in contract structures and asset ownership that require clearer legal guidelines. This study is expected to contribute to the development of contemporary fiqh muamalah concepts.